Performance of perovskite solar cell coated with graphene oxide as hole transport layer - Hatib, Rustan; Soeparman, Sudjito; Widhiyanuriyawan, Denny; Hamidi, Nurkholis (Eastern-European Journal of Enterprise Technologies, 2021)
Organic metal halide perovskite has recently shown great potential for applications, as it has the advantages of low cost, excellent photoelectric properties, and high power conversion efficiency. The Hole Transport Material (HTM) is one of the most critical components in Perovskite Solar Cells (PSC). It has the function of optimizing the interface, adjusting the energy compatibility, and obtaining higher PCE. The inorganic p-type semiconductor is an alternative HTM due to its chemical stability, higher mobility, increased transparency in the visible region, and general valence band energy level (VB). Here we report the use of the Graphene Oxide (GO) layer as a Hole Transport Layer (HTL) to improve the perovskite solar cells’ performance. The crystal structure and thickness of GO significantly affect the increase in solar cell efficiency. This perovskite film must show a high degree of crystallinity. The configuration of the perovskite material is FTO/NiO/GO/CH3NH3PbI3/ZnO/Ag. GO as a Hole Transport Layer can increase positively charged electrons’ mobility to improve current and voltage. As a blocking layer that can prevent recombination. The GO can make the perovskite interface layer with smoother holes, and molecular uniformity occurs to reduce recombination. The method used in this study is by using spin coating. In the spin-coating process, the GO layer is coated on top of NiO with variations in the rotation of 700 rpm, 800 rpm, 900 rpm, 1,000 rpm, and 1,500 rpm. The procedure formed different thicknesses from 332.5 nm, 314.7 nm, 256.4 nm, 227.4 to 204.5 nm. The results obtained at a thickness of 227.4 nm reached the optimum efficiency, namely 15,3 %. Thus, the GO material as a Hole Transport Layer can support solar cell performance improvement by not being too thick and thin